Structural behavior of a new moment-resisting DfD concrete connection. (1st February 2017) - Xiao, Jianzhuang; Ding, Tao; Zhang, Qingtian
Highlights: A novel moment-resisting DfD connection for concrete frame joints was proposed. The new DfD connection was evaluated under both static and cyclic flexural loadings. Both NAC and RAC are feasible to be adopted in DfD connections effectively. Abstract: Design for deconstruction (DfD) is a burgeoning concept in civil engineering. DfD building components have the possibility to be reused as a second life at the end of the building's first service life. A simple moment-resisting DfD concrete connection for concrete frame joints was proposed in this study. Five full-scale specimens were tested to explore the effectiveness and limitations of the new developed DfD concrete connections. Both static and cyclic flexural loading tests were conducted. Beams made of natural aggregate concrete (NAC) or recycled aggregate concrete (RAC) were extended from column faces. Test results confirmed that the achievement of reinforcement continuity significantly improved the structural behavior of DfD concrete connections. The proposed DfD concrete connections, made of NAC and RAC demonstrated favorable ductility under static and cyclic loadings respectively. In addition, mechanical removal process was easy during the deconstruction stage on account of little post-cast concrete.